Silencing of proinflammatory NF-κB and inhibition of herpes simplex virus (HSV) replication by ultrasmall gold nanoparticles (2 nm) conjugated with small-interfering RNA. Issue 21 (9th September 2022) - Wolff, Natalie; Kollenda, Sebastian; Klein, Kai; Loza, Kateryna; Heggen, Marc; Brochhagen, Leonie; Witzke, Oliver; Krawczyk, Adalbert; Hilger, Ingrid; Epple, Matthias
Abstract : Different kinds of alkyne-terminated siRNA duplexes were conjugated to azide-terminated ultrasmall gold nanoparticles (2 nm) via copper-catalyzed azide–alkyne cycloaddition, depending on the gene to be silenced. Abstract : Azide-terminated ultrasmall gold nanoparticles (2 nm gold core) were covalently functionalized with alkyne-terminated small-interfering siRNA duplexes by copper-catalyzed azide–alkyne cycloaddition (CuAAC; click chemistry). The nanoparticle core was visualized by transmission electron microscopy. The number of attached siRNA molecules per nanoparticle was determined by a combination of atomic absorption spectroscopy (AAS; for gold) and UV-Vis spectroscopy (for siRNA). Each nanoparticle carried between 6 and 10 siRNA duplex molecules which corresponds to a weight ratio of siRNA to gold of about 2.2 : 1. Different kinds of siRNA were conjugated to the nanoparticles, depending on the gene to be silenced. In general, the nanoparticles were readily taken up by cells and highly efficient in gene silencing, in contrast to free siRNA. This was demonstrated in HeLa-eGFP cells (silencing of eGFP) and in LPS-stimulated macrophages (silencing of NF-κB). Furthermore, we demonstrated that nanoparticles carrying antiviral siRNA potently inhibited the replication of Herpes simplex virus 2 (HSV-2) in vitro . This highlights the strong potential of siRNA-functionalized ultrasmall gold nanoparticles in a broad spectrum of applications, including gene silencing and treatment of viral infections, combined with a minimal dose of gold.